1987
DOI: 10.2105/ajph.77.9.1180
|View full text |Cite
|
Sign up to set email alerts
|

Brain cancer and nonoccupational risk factors: a case-control study among workers at two nuclear facilities.

Abstract: In a nested case-control study of nuclear workers, 82 brain cancer cases were compared with 328 matched controls to investigate the possible association with nonoccupational risk factors such as histories of epilepsy or head injury. We observed a moder-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Comparing 82 patients with brain tumour to a control group of 328 subjects, Carpenter et al [7] found no significant association with a previous head injury. Scheid [38], analysing 14,445 patients with gunshotinjuries, found only 6 brain tumours.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparing 82 patients with brain tumour to a control group of 328 subjects, Carpenter et al [7] found no significant association with a previous head injury. Scheid [38], analysing 14,445 patients with gunshotinjuries, found only 6 brain tumours.…”
Section: Discussionmentioning
confidence: 98%
“…The following aspects deserve comment when the relationship between a brain tumour and previous head injury is considered: [25,26] 14,000 head injury no Scheid [38] 14,445 gunshot injury no Carpenter et al [7] 82 primary brain tumour no Hochberg et al [ 16J 160 glioblastoma no a, yes b Parker and Kernohan [28] 431 glioma no Preston-Martin et al [33] 202 glioma no 70 meningioma yes a Patient younger than 15 years at the time of the trauma. b Patient older than 15 years at the time of the trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Inskipp et al [12] suggested that severe head trauma slightly increases the overall risk of brain tumors. Similarly, Salvati et al [21] believe in an etiological association between severe head trauma and glioma development whereas others [22][23][24] consider that there is no clear correlation between cranial trauma and subsequent glioma formation. However, these studies included all types of head injuries (mild, moderate and severe) and could not rule out the possible effect of a severe cranial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Severson et al (25), the risk of childhood acute myeloid leukemia among children who were diagnosed at two years of age or younger was signi cantly associated with mothers' alcohol use during their pregnancies (25), while in another study, no association was found between reported fathers' consumption of alcohol and childhood cancer (26). Although epidemiologic studies have not found an increased risk of brain cancer in adults related to alcohol consumption (27)(28)(29)(30)(31)(32)(33)(34)(35), with the exception of one which found an increased risk with consumption of wine (30) and our previous report of increased risk among males for hard liquor consumption (14), our present ndings suggest that fathers' consumption of hard liquor may play an important role in the development of brain cancer in their offspring.…”
Section: Discussionmentioning
confidence: 99%